The phylogenetic relevance of pollen grain size in legumes: a study case with Adesmia DC. and relatives (Leguminosae–Papilionoideae–Dalbergieae–Adesmia Informal Clade) - Antonio-Domingues, Higor; Fortuna-Perez, Ana Paula [UNESP]; Rossi, Mônica Lanzoni; Almeida, Rafael Felipe de; Martinelli, Adriana Pinheiro; Lewis, Gwilym Peter; Luz, Cynthia Fernandes Pinto da (Taylor & Francis, 2024)
Adesmia is the most species-rich genus in the informal Adesmia clade and temperate South America Leguminosae. The pollen morphology, ultrasculpture, and ultrastructure of 25 species of Adesmia were studied using light, scanning, and electron transmission microscopy to explore micromorphological data informative to the taxonomy of the genus. Additionally, a principal component analysis was performed to elucidate patterns of quantitative data variation among species concerning the most recent molecular data. We provide novel data about the genus, a comprehensive description of the pollen grains and sexine ultrasculpture, and descriptions of the exine ultrastructure. Furthermore, we suggest delimiting two pollen types based on the size of equatorial and polar axis dimensions to help in future palynotaxonomic studies and character optimisation focusing on pollen traits.
Keywords: Dalbergia clade; Fabaceae; palynology; pollen morphology; South America